Reducing mineral and vitamin deficiencies through biofortification: Progress under HarvestPlus - Bouis, Howarth E. (Karger AG, 2018)
HarvestPlus estimates that 20 million farmers and consumers presently grow and consume biofortified crops in 8 target countries. The final and major challenge is to mainstream biofortification into the fabric of “business-as-usual” of a range of organizations - public and private agricultural research, institutions that focus on bringing improved agricultural technologies to farmers including multi-lateral lending institutions, private companies, non-governmental organizations, and the policies and programs of national governments, regional organizations, and UN agencies.